Problematika Sistem Pendidikan di Indonesia - Yekti Handayani; Sukari Sukari (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2025)
This study aims to identify the main problems in the Indonesian education system and offer applicable solutions to overcome them. Using qualitative descriptive methods, data were obtained through literature studies and document analysis from various reliable sources. This study found that the main challenges of education in Indonesia include low teacher quality, inequality in education, high education costs, curriculum complexity, and minimal facilities and infrastructure. These factors have a significant impact on the overall low quality of education. The results of this study are expected to provide new insights into efforts to improve the quality of education in Indonesia through innovative and sustainable strategies.